1994
DOI: 10.1126/science.8079174
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Sphingomyelin Cycle Through the Low-Affinity Neurotrophin Receptor

Abstract: The role of the low-affinity neurotrophin receptor (p75NTR) in signal transduction is undefined. Nerve growth factor can activate the sphingomyelin cycle, generating the putative-lipid second messenger ceramide. In T9 glioma cells, addition of a cell-permeable ceramide analog mimicked the effects of nerve growth factor on cell growth inhibition and process formation. This signaling pathway appears to be mediated by p75NTR in T9 cells and NIH 3T3 cells overexpressing p75NTR. Expression of an epidermal growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
369
0
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 577 publications
(381 citation statements)
references
References 42 publications
10
369
0
2
Order By: Relevance
“…A number of extracellular stimuli, not only various cytokines including tumor necrosis factor (TNF)-a, interferon-g (Kim et al, 1991;Dressler et al, 1992), interleukin-1b (Ballou et al, 1992), nerve growth factor (Dobrowsky et al, 1994), and activators of Fas receptor (Cifone et al, 1994), but also physical stresses including heat shock, irradiation and chemotherapeutic drugs (Verheij et al, 1996;Santana et al, 1996;Ja rezou et al, 1996) are shown to cause sphingomyelin (SM) hydrolysis via sphingomyelinase (SMase), leading to elevation of intracellular ceramide, although several recent reports have questioned the role of ceramide in apoptosis induced by Fas or TNF-a (Sillence and Allen, 1997; Hsu et al, 1998;Watts et al, 1997Watts et al, , 1999a. The addition of exogenous ceramide has been associated with several antiproliferative responses including cell di erentiation, apoptosis, and cell cycle arrest (Okazaki et al, 1990;Kolesnick and Hannun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A number of extracellular stimuli, not only various cytokines including tumor necrosis factor (TNF)-a, interferon-g (Kim et al, 1991;Dressler et al, 1992), interleukin-1b (Ballou et al, 1992), nerve growth factor (Dobrowsky et al, 1994), and activators of Fas receptor (Cifone et al, 1994), but also physical stresses including heat shock, irradiation and chemotherapeutic drugs (Verheij et al, 1996;Santana et al, 1996;Ja rezou et al, 1996) are shown to cause sphingomyelin (SM) hydrolysis via sphingomyelinase (SMase), leading to elevation of intracellular ceramide, although several recent reports have questioned the role of ceramide in apoptosis induced by Fas or TNF-a (Sillence and Allen, 1997; Hsu et al, 1998;Watts et al, 1997Watts et al, , 1999a. The addition of exogenous ceramide has been associated with several antiproliferative responses including cell di erentiation, apoptosis, and cell cycle arrest (Okazaki et al, 1990;Kolesnick and Hannun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…p75 NTR has been shown to enhance NGF binding and signaling through TrkA (51)(52)(53)(54). p75 NTR also initiates signal transduction separately from TrkA (55)(56)(57). There is increasing evidence that the signals generated by p75 NTR promote programmed cell death (58)(59)(60)(61) rather than prevent it, as does TrkA (62).…”
Section: Resultsmentioning
confidence: 99%
“…As for specific sets of neurons, 53 p75 LNGFR may modulate the interaction of a defined NT to its specific Trk receptor on bone marrow stromal cells. p75 LNGFR also signals on its own 54 and triggers neuronal apoptosis in the absence of NGF-induced TrkA activation. 55,56 The generation of TK ϩ or TK-receptor isoforms, which retain NT high-affinity binding sites, may also modulate the local function of NT.…”
Section: Discussionmentioning
confidence: 99%